LEGITIMASI POLITIK DI MAKAM TUAN GURU: PERILAKU ZIARAH POLITISI LOKAL KE - Ziaulhaq* Ziaulhaq* (At-Tafkir, 2014)
This article is related to politicians’ ziarah act to TarekatNaqsyabandiyah Babussalam (TNB). TNB is a phenomena that isalways related to political moment such as regional election and legislativeelection. The phenomena is important to be showed about how localpoliticians’ ziarah act in TNB. This articles’ objective is to answer thequestions have been proposed. As long the research has been done, can befound that local politicians’ ziarah act in TNB is to get the master’spraying and members’ praying. In ziarah activity there are reciting Yasin41 and praying in front of the founder’s funeral. As a legitimation forpolitician can be seen as follow: publication of ziarah activity on printedmedia and electronic media; putting the master’s photograph on bannersin public sphere; coming to haul of TNB; and using TNB’s activity.